Toxoplasma gondii-Driven Cytokine Dysregulation as a Differentiating Biomarker Between Schizophrenia and Depression - Lathifatul Azka Nurul Aini; Dita Pratiwi Kusuma Wardani; Isna Hikmawati; Ikhsan Mujahid (CV. Rayyan Dwi Bharata, 2026)
Schizophrenia and depression are among the most prevalent psychiatric disorders, and both have been mechanistically linked to systemic and neuroinflammatory processes. Infection with the protozoan parasite Toxoplasma gondii has been proposed as a potential trigger of these inflammatory pathways, yet direct comparisons of proinflammatory cytokine profiles between the two disorders in the context of T. gondii infection remain scarce. Consequently, it is still unclear whether schizophrenia and depression share a common toxoplasmosis-associated inflammatory signature or instead display distinct immunological fingerprints. This systematic review aimed to characterize the proinflammatory cytokine biomarker patterns—particularly IL-6, IFN-γ, and TNF-α—among T. gondii-infected patients with schizophrenia and depression. Conducted in accordance with the PRISMA 2020 guidelines and the PICO framework, the review searched PubMed Central, PubMed, ScienceDirect, and Scopus for original English-language studies published between 2021 and 2025. Of 454 records initially retrieved and screened for eligibility using Mendeley Reference Manager, five studies satisfied all inclusion criteria. The synthesis revealed that toxoplasmosis-associated schizophrenia was characterized by elevated MCP-1, RANTES, GRO-α, IP-10, and IL-8, along with reduced MIP-1α, MIP-1β, and IL-8, whereas toxoplasmosis-associated depression was primarily characterized by increased IL-6 and TNF-α. These divergent cytokine patterns suggest that chronic T. gondii infection induces disorder-specific immune dysregulation rather than a uniform inflammatory response. Such distinct profiles may hold promise as biomarkers for differentiating infection-related psychiatric subtypes and could inform the development of more targeted, immunomodulatory therapeutic strategies for affected patients